Induction FOLFIRINOX followed by stereotactic body radiation therapy in locally advanced pancreatic cancer - Jung, Jae Hyup; Song, Changhoon; Jung, In Ho; Ahn, Jinwoo; Kim, Bomi; Jung, Kwangrok; Lee, Jong-Chan; Kim, Jaihwan; Hwang, Jin-Hyeok (Frontiers in Oncology, 2022)
Introduction FOLFIRINOX (the combination of 5-fluorouracil, leucovorin, irinotecan, and oxaliplatin) is the preferred systemic regimen for locally advanced pancreatic cancer (LAPC). Furthermore, stereotactic body radiation therapy (SBRT) is a promising treatment option for achieving local control in these patients. However, clinical outcomes in patients with LAPC treated using FOLFIRINOX followed by SBRT have not been clarified. Therefore, we aimed to evaluate clinical outcomes of induction FOLFIRINOX treatment followed by SBRT in patients with LAPC. Methods To this end, we retrospectively reviewed the medical records of patients with LAPC treated with induction FOLFIRINOX followed by SBRT in a single tertiary hospital. We evaluated overall survival (OS), progression-free survival (PFS), resection rate, SBRT-related adverse events, and prognostic factors affecting survival. Results Fifty patients were treated with induction FOLFIRINOX for a median of 8 cycles (range: 3–28), which was followed by SBRT. The median OS and PFS were 26.4 (95% confidence interval [CI]: 22.4–30.3) and 16.7 months (95% CI: 13.0–20.3), respectively. Nine patients underwent conversion surgery (eight achieved R0) and showed better OS than those who did not (not reached vs. 24.1 months, p = 0.022). During a follow-up period of 23.6 months, three cases of grade 3 gastrointestinal bleeding at the pseudoaneurysm site were noted, which were managed successfully. Analysis of the factors affecting clinical outcomes revealed that a high radiation dose (≥ 35 Gy) resulted in a higher rate of conversion surgery (25% [8/32] vs. 5.6% [1/18], respectively) and was an independent favorable prognostic factor for OS in the adjusted analysis (hazard ratio: 2.024, 95% CI: 1.042–3.930, p = 0.037). Conclusion Our findings suggest that induction FOLFIRINOX followed by SBRT in patients with LAPC results in better survival with manageable toxicities. A high total SBRT dose was associated with a high rate of conversion surgery and could afford better survival.